A Final Utterance: The Last Words of Sir Isaac Brock - St-Denis, Guy (Ontario History, 2018)
After more than 200 years and much confusion surrounding Brock’s last words, it is not surprising that there should be a growing consensus in favour of a silent death. Yet, while modern interpretations have concluded that Brock’s fatal wound prevented him from saying anything, several eye-witness accounts suggest otherwise—even going so far as to contradict his famous battle cry: “Push on the brave York Volunteers!” As part of his on-going research into the life and generalship of Canada’s War of 1812 hero, Guy St-Denis offers an analysis of all the surviving evidence for a better understanding of Brock’s final utterance.